Pattern of Skin Diseases in Patients Attending OPD of Dermatology and Venereology in a Tertiary Care Hospital in Bangladesh - Alahi, Mohammad Niamat; Hossain, Md Anowar; Mohammad, Abu Sayeed (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Skin diseases account for a higher proportion of outpatient department in developing countries including Bangladesh. Objective: The purpose of the present study was to evaluate the pattern of skin diseases in patients attending OPD of Dermatology and venereology in a tertiary care hospital. Methodology: This cross-sectional study was conducted in the outpatient department of medical college hospital of Kishoreganj in Bangladesh from 2013 to 2016 for a period of four (4) years. All the patients at any age and sex who were attended in the OPD of the hospital selected as study population. Only newly diagnosed cases were included in the study. The socio-demographic profiles and diseases pattern were recorded in a data sheet. Diagnosis was made on clinical basis by expert dermatologist. Lab investigations were restricted to the cases where it carried diagnostic importance. Result: A total number of 119228 patients (near about 82/day) were recruited for this study. Out of them 57825 (48.5%) cases were male and 61403 (51.5%) cases were female. Infective diseases were more common than non-infective diseases which were (65409; 54.9%) and (53819; 45.1%) cases respectively. In cases of infective diseases; parasitic, fungal, bacterial, viral, sexually transmitted infection and other nonspecific infections were 20408(31.2%), 17464(26.7%), 12166(18.6%), 8503(13.0%), 3597(5.5%) and 3271(5.0%) respectively. Out of 20408 parasitic diseases of which 20061(98.3%) cases were scabies and 1347(1.7%) cases were pediculosis. Out of 17464 fungal diseases tinea capitis, tinea corporis, tinea cruris, candidiasis, onychomycosis and pityriasis versicolor were found in 2655(15.2%) cases, 3737(21.4%) cases, 3423(19.6%) cases, 3127(17.9%) cases, 1031(5.9%) cases and 3492(20.0%) cases respectively. Out of 12166 bacterial diseases Impetigo was found in 4745(39.0%) cases, pyoderma in 4282(35.2%) cases, folliculitis in 3103(25.5%) cases, leprosy in 24(0.2%) cases and skin TB in 12(0.1%) cases. Among the viral diseases verruca was found in 4056(47.7%) cases. In case of non-infective diseases, eczema, papulo-squamous disease, acne, urticarial, drug reaction, vitiligo, chronic arsenicosis, neoplastic skin disorder, genodermatoses and others were 16953(31.5%), 9903( 18.4%),7696( 14.3%), 8019( 14.9%), 4682( 8.7%), 2099( 3.9%), 269(0.5%), 161(0.3%), 431(0.8%) and 3606( 6.7%) respectively. Conclusion: In conclusion, we found that a huge burden of skin diseases are present in the OPD. Infective skin diseases mostly bacterial and parasitic still predominant in Bangladesh though it is less frequent in developed countries. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 116-122